2016
DOI: 10.14444/3032
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging of the Cervical Spine Under-Represents Sagittal Plane Deformity in Degenerative Myelopathy Patients

Abstract: We would recommend the use of standing x-rays when considering surgical planning in all myelopathy patients. This manuscript was reviewed and approved by an institutional review board. Informed consent was not obtained because patient specific identifying information was not used. It was performed in accordance with the ethical standards laid down in the 1964 Declaration of Helsinki and its later amendments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…2,[11][12][13][14] While direct comparisons are limited, the differences in the findings and conclusions are notable and summarized in Table 3. In a related study consisting of 101 patients with cervical myelopathy, Weinberg et al 18 found significant differences in cervical curvature angle This study has several limitations. Our patient cohort was defined as patients who underwent posterior-based cervical surgery for cervical spondylotic myelopathy; all patients had either a laminoplasty or laminectomy with fusion.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…2,[11][12][13][14] While direct comparisons are limited, the differences in the findings and conclusions are notable and summarized in Table 3. In a related study consisting of 101 patients with cervical myelopathy, Weinberg et al 18 found significant differences in cervical curvature angle This study has several limitations. Our patient cohort was defined as patients who underwent posterior-based cervical surgery for cervical spondylotic myelopathy; all patients had either a laminoplasty or laminectomy with fusion.…”
Section: Discussionmentioning
confidence: 77%
“…Oftentimes, in the workup of patients with clinical signs and symptoms of cervical spondylotic myelopathy, MRI is the primary imaging modality used to characterize central spinal cord and nerve root compression 16,17. The nearly ubiquitous nature of MR imaging in spinal care has led some healthcare providers, and even payors, to question the utility of obtaining radiographs in the setting of an existing magnetic resonance imaging 18. Upright lateral radiographs, however, have traditionally been the gold standard to assess sagittal alignment and are thought to be necessary for preoperative surgical planning.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations